Efficacy of an asynchronous electronic curriculum in emergency medicine education in the United States - Wray, Alisa (J Educ Eval Health Prof, 2017)
PURPOSE: The aim of this study was to measure the effect of an iPad-based asynchronous curriculum on emergency medicine resident performance on the in-training exam (ITE). We hypothesized that the implementation of an asynchronous curriculum (replacing 1 hour of weekly didactic time) would result in non-inferior ITE scores compared to the historical scores of residents who had participated in the traditional 5-hour weekly didactic curriculum. METHODS: The study was a retrospective, non-inferiority study. conducted at the University of California, Irvine Emergency Medicine Residency Program. We compared ITE scores from 2012 and 2013, when there were 5 weekly hours of didactic content, with scores from 2014 and 2015, when 1 hour of conference was replaced with asynchro-nous content. Examination results were compared using a non-inferiority data analysis with a 10% margin of difference. RESULTS: Using a non-inferiority test with a 95% confidence interval, there was no difference between the 2 groups (before and after implementation of asynchronous learning), as the confidence interval for the change of the ITE was −3.5 to 2.3 points, whereas the 10% non-inferiority margin was 7.8 points. CONCLUSION: Replacing 1 hour of didactic conference with asynchronous learning showed no negative impact on resident ITE scores.